Optimalisasi LinkedIn : Pendampingan Literasi Digital dan Kesiapan Karier Mahasiswa Calon Guru dan Profesional Lintas Bidang - Zaitun Qamariah; Hesty Widiastuty; Hadma Yuliani (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
The digital transformation era requires university students to develop digital literacy competencies that not only support academic activities but also serve as essential capital for entering the workforce and pursuing entrepreneurship. One relevant professional platform to enhance career readiness is LinkedIn, which serves as a medium for both personal branding and professional networking. This community service aimed to improve students’ digital literacy and career readiness through mentoring sessions on LinkedIn account optimization. The program involved the students from the English Education (TBI) and Physics Education (TFS) study programs at the Faculty of Tarbiyah and Teacher Training, UIN Palangka Raya, comprising prospective teachers and professionals across various disciplines. The implementation was carried out through tutorials and direct mentoring in two sessions, covering account creation, developing professional headlines and summaries, adding skills and experiences, and uploading simple portfolios. The results indicated that all participants successfully created or improved their LinkedIn profiles, actively engaged in the activities, and demonstrated a greater awareness of the importance of a professional digital identity, which can be seen from the students’ participation, the quality of the profiles produced, and their commitment to continuously developing their LinkedIn accounts. The program highlights LinkedIn’s strategic role in strengthening digital literacy and career readiness among university students in the global era.